论郭德纲对传统相声的继承与创新 = A study of Guo Degang's artistic preservation and innovation of the traditional crosstalk (Xiang Sheng) - 王丹 Wang, Dan (2015)
相声是民间艺术的发展与壮大，发源于中国华北地区，初期流行于京、津一带。在150年的建行历史中经历了跌宕起伏的改革变化，1949年中华人民共和国成立，“去糟取精”后地位稳步上升，但由于过“雅”以及其 它娱乐形式的崛起等一系列主客观问题而逐渐失去了观众群体。相声艺人不断改革创新，试图挽救相声式微的局面，其中郭德纲的“传统相声”不可小觑，深受观众的认可和追捧，但其发展却受到来自“主流”相声艺术 家们的阻碍。本文将先梳理相声的发展脉络并以此为背景，再重点分析郭氏相声对 传统的继承与创新两方面的成败优劣，在反思“郭德纲现象”的同时，进一步剖析关于郭德纲相声“非主流”和“非传统”的争议，并从郭氏个例得出对传统艺术复兴的启迪。Crosstalk is a traditional Chinese comedic that originated in North China and prevailed in the area of Beijing and Tianjin. Since its emergence in late Qing Dynasty, it experienced tremendous changes over the 150 years. After the establishment of People’s Republic of China in 1949, Crosstalk’s artistic position had improved due to is success in content revolution. However, it became too political-oriented time after time, together with the rise of other forms of amusement and challenge, crosstalk put itself in a predicament and lost many of its audience. Guo Degang is one of the Crosstalk comedians who have tried to keep this traditional art alive. His success is undeniable due to the enormous group of audiences that support him. Nevertheless, Guo’s Traditional Crosstalk is accused for being barbaric and non-authentic. This thesis sets off to provide a clear view of his artistic representations of traditional Crosstalk, as well as a rational analysis toward various disputes relates to Guo’s Crosstalk. Moreover, to inspires the revival of other traditional arts.